Expressão heteróloga e modelagem de uma enzima lipolítica utilizando a abordagem metagenômica - Garcia, Rosmeriana Áfnis Marioto [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The metagenomics is a powerful tool in the discovery of new microbial genes with biotechnological potential, they are not necessary traditional cultivation techniques. With increasing demand for enzymes in the market this technique has been widely used for the discovery of new genes encoding microbial lipases and esterases widely used in biotechnological processes such as the production of detergents, biodiesel and bioremediation. In previous work, coding sequences for lipolytic enzymes were prospected in 4224 clones from a metagenomic DNA library from a microbial consortium obtained from soil contaminated with petroleum hydrocarbons, located in the city of Ribeirão Preto - São Paulo - Brazil, obtaining 30 clones with possible lipase activity on tributyrin. In this study, one clone was selected after testing in a Petri dish with Tributyrin to build a sub-library, with 480 subclones. Sequencing was performed on ABI PRISM 3100 instrument and analyzed “contig”s obtained in the ORF finder from the National Center for Biotechnology Information (NCBI, Bethesda, Maryland, USA). It was possible to identify a gene of 1032 bp, 344 amino acids, termed ORF2, encoding a lipolytic enzyme with 94% identity with a hydrolase from Pseudomonas denitrificans (YP_007656829.1). The sequences representing eight families of lipolytic enzymes and Arpying proposed by Jaeger (1999) were extracted from the NCBI database and compared with the sequence of ORF2, allowing affirm that this enzyme is a new member of the family V bacterial lipolytic enzymes . The encoder ORF2 gene was cloned into pET28a expression vector and overexpressed in Escherichia coli BL21 (D3). The soluble protein fraction was analyzed by polyacrylamide (SDS-PAGE) gel in denaturing condition. The lipolytic activity of the recombinant protein bands on the SDS-PAGE gel was confirmed by a zymogram indicating its functionality in a specific substrate. Three-dimensional modeling was also ...

A metagenômica é uma ferramenta poderosa na descoberta de novos genes microbianos com potencial biotecnológico, pois não são necessárias as técnicas tradicionais de cultivo. Para suprir as necessidades de enzimas no mercado esta técnica tem sido muito utilizada para a descoberta de novos genes codificadores de lipases e esterases microbianas muito utilizadas em processos biotecnológicos como produção de detergentes, biodiesel e biorremediação. Em trabalhos anteriores, foram prospectadas sequências codificadoras para enzimas lipolíticas em uma biblioteca metagenômica de DNA com 4224 clones, de um consórcio microbiano obtido de solo contaminado com hidrocarbonetos de petróleo, localizado na cidade de Ribeirão Preto – São Paulo - Brasil, obtendo-se 30 clones com possível atividade lipolítica em Tributirina. No presente trabalho, um dos clones foi selecionado após ensaio em placa de Petri com Tributirina para a construção de uma sub-biblioteca, com 480 subclones. O sequenciamento foi realizado em aparelho ABI Prism 3100 e o “contig” obtido analisado no ORF Finder do National Center for Biotechnology Information (NCBI, Bethesda, Maryland, USA). Foi possível identificar um gene de 1032 pb, 344 aminoácidos , denominado ORF2, que codifica uma enzima lipolítica com identidade de 94 % com uma hidrolase de Pseudomonas denitrificans (YP_007656829.1). As sequências que representam as oito famílias de enzimas lipolíticas propostas por Arpying e Jaeger (1999) foram extraídas do banco de dados do NCBI e comparadas com a sequência da ORF2, possibilitando afirmar que esta enzima é um novo membro da família V de enzimas lipolíticas bacteriana. O gene codificador da ORF2 foi clonado em vetor de expressão pET28a e superexpressado em Escherichia coli BL21(D3). A fração solúvel da proteína foi analisada em gel de poliacrilamida (SDS-PAGE), em condição desnaturante. A atividade lipolítica das bandas da proteína ...
Keywords: Enzimas; Esterases; Lipase; Proteínas; Genes; Enzymes